Pembelajaran Penemuan Berbasis Teori Bruner Untuk Meningkatkan Kemampuan Penalaran Matematis Siswa Kelas III SD/MI di Kabupaten Bayumas - Novikasari, Ifada; Rahmawati, Lily; Muflihin, Hizbul; Mutijah; Rohmad (Jurnal keilmuan dan Kependidikan dasar, 2025)
This study aimed to test the effectiveness of Bruner’s theory-guided discovery learning in enhancing the mathematical reasoning ability of elementary school students. The study was done with a quasi-experimental design and an experimental group instructed with discovery learning based on Bruner’s theory was compared with a control group instructed expositively. he population of this study consisted of elementary schools (SD/MI) in Banyumas Regency with accreditation levels A and B, totaling 38 schools. Using a stratified random sampling technique, four schools were selected—each representing schools with accreditation A and B—and were assigned as the experimental and control groups. The findings indicate that the experimental group significantly enhanced the ability to identify patterns, generalize, and construct and test mathematical arguments compared to the control group. However, the post-test scores suggest that students’ reasoning abilities in the experimental group have not reached a maximum point, possibly because they had not been exposed to enough experience in exploratory learning. The ANOVA test also failed to reveal any significant interaction between school accreditation category and instruction type on the student’s mathematical reasoning ability. With well-planned deployment and even more tailored to students’ characteristics, Bruner’s theory-guided discovery learning has immense potential to improve the quality of mathematics education at the elementary school level.